Analysis of the Influence of Digital Marketing on Increasing MSME Sales in Bima City - Afiah, Syagiratul; Yuliati, Rosa; Nurwahidah, Nurwahidah (Business Management, 2026)
This Study aims to analyze the influence of digital marketing on increasing sales UMKM at Bima City by focusing various elemens of digital marketing. The research method used quantitative research with an associative approarch which is a study that aims to determine the relatioship between two or more variables. The sample of research used purposive sampling with a sample of 120 UMKM in Bima City with 2 criteria: 1) UMKM bisnis in Bima City, 2) maximum assets of 100 million. Data were analyzed using SPSS 25 with data quality test methods, classical assumption test and determinant coefficients.